RELATIONSHIP OF LIPID PROFILE AND IMMUNE STATUS IN THE DYNAMICS OF LONG-TERM EXPOSURE TO COAL-ROCK DUST ON THE BODY (EXPERIMENTAL STUDIES) - Анастасия Сергеевна Казицкая; Анна Геннадьевна Жукова; Мария Сергеевна Бугаева; Наталья Николаевна Жданова (Медицина в Кузбассе)
Subject. The relationship between lipid metabolism and immune reactivity in the dynamics of long-term exposure to coal-rock dust (CRD) on the body.